Long-term effects of orchard soil management practices on growth, yield and fruit quality of apple (Malus domestica) - KUMAR, JAYANT; REHALIA, A S; RANA, S S; VERMA, H S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1987-95 at Bajaura to study the effect of 5 orchard soil managementpractices, viz herbicide plus mulching with hay,herbicide, mulching with hay, mulching with white netted polytheneand clean cultivation on growth, yield and fruit quality of 'Starking Delicious' apple (Malus domestica Borich.) graftedon M7 rootstock. The highest trunk girth (55.8 cm), shoot length (46.6 cm) and fruit yield (89.4 kg/tree) was observedwith herbicide plus mulching with hay followed by herbicide alone. The lowest trunk girth (52.4 cm), shoot length (32.8cm) and fruit yield (66.6 kg/tree) was recorded with clean cultivation. The treatment herbicide plus mulching with hayresulted in the highest fruit length (7.20 cm), fruit breadth (7.48 cm) and fruit weight (260.4 g) followed by mulchingwith hay. The lowest fruit length (6.78 cm), fruit breadth (6.97 cm) arid fruit weight (232.6 g) was observed with cleancultivation. However, the clean cultivation resulted in the highest total soluble solids (15.1 O S). Other quality traits werenot influenced. The treatment herbicide plus mulching with hay Can be recommended for apple orchards.